2019
DOI: 10.1167/iovs.18-25556
|View full text |Cite
|
Sign up to set email alerts
|

Development of aPde6bGene Knockout Rat Model for Studies of Degenerative Retinal Diseases

Abstract: Citation: Yeo JH, Jung BK, Lee H, et al. Development of a Pde6b gene knockout rat model for studies of degenerative retinal diseases. Invest Ophthalmol Vis Sci. 2019;60:1519-1526. https://doi.org/10.1167/ iovs.18-25556 PURPOSE. To describe the phenotypes of a newly developed Pde6b-deficient rat model of retinal degeneration.METHODS. Pde6b knockout rats were produced by CRISPR-Cpf1 technology. Pde6b knockout rats were evaluated for ocular abnormalities by comparison with wild-type eyes. Eyes were imaged using f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
(35 reference statements)
0
18
0
Order By: Relevance
“…3a ). We generated a Pde6b knockout rat model as a retinal degeneration model that typically shows generalized retinal cell damage and reduced retinal thickness 3 weeks after postnatal development 18 . Cells were injected before the expected appearance of retinal damage at 2–3 weeks of age to decelerate retinal degeneration, and support the recovery of RPE cell and photoreceptor function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3a ). We generated a Pde6b knockout rat model as a retinal degeneration model that typically shows generalized retinal cell damage and reduced retinal thickness 3 weeks after postnatal development 18 . Cells were injected before the expected appearance of retinal damage at 2–3 weeks of age to decelerate retinal degeneration, and support the recovery of RPE cell and photoreceptor function.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we demonstrated for the first time that human iPSC (hiPSC)-derived retinal cells that can differentiate into both photoreceptors and RPE cells can efficiently rescue the degenerated host retina. Using a Pde6b knockout rat model, which is a novel model of RP established using CRISPR-Cpf1 technology 18 , we found that transplanted hiPSC-derived retinal cells can survive in the host retina for a long time and restore retinal function.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of genes associated with the inflammatory response - such as Ifi44l , Serpina3n , S100a6 , Bcl3 , and Gfap - was also increased in the Prom1 -KO retina at P21. Conversely, the expression of genes related to RP or of those essential for retinal development and functional homeostasis - including Fscn2 (RP30) [19], Prph2 (RP7) [20], Nr2e3 (RP37) [21], Kcnv2 [22], Elovl2 [23], Pde6b (RD1) [24], and Ttc21b [25] - was down-regulated in the Prom1 -KO retina at P21 (supplementary table S3). GO term analysis revealed that several signalling pathways, including apoptotic (TNF) and infectious-related signal (Epstein-Barr virus infection) signals, were affected by the loss of Prom1 (figure 3 c ).…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, some orthologs of Cpf1 (Cas12a) are the most used after SpCas9, including Acidaminococcus sp. (AsCpf1) (Lee J. G. et al, 2019;Yeo et al, 2019) and Lachnospiraceae bacterium ND2006 (LbCpf1) (Lee J. G. et al, 2019).…”
Section: Crispr-cas Systemsmentioning
confidence: 99%